2013
DOI: 10.1080/1331677x.2013.11517626
|View full text |Cite
|
Sign up to set email alerts
|

Does Idiosyncratic Volatility Matter in the Emerging Markets? Istanbul Stock Exchange Evidence

Abstract: In finance literature, Capital Asset Pricing Model predict only systematic risk is priced in equilibrium and neglect firm specific (idiosyncratic) risk which can be eliminated by diversification. However in real world investors, who are disable to diversify their portfolios, should take into consideration idiosyncratic risk beside of systematic risk in prediction of expected return. In this article, we examine real market conditions in Istanbul Stock Exchange (ISE), an emerging market stock exchange, over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Traditionally, the Capital Asset Pricing Model (CAPM) has focused on systematic risk, overlooking firm-specific (idiosyncratic) risk, which can't be diversified away. However, in practical scenarios where portfolio diversification isn't feasible, investors must account for idiosyncratic risk alongside systematic risk in predicting expected returns (Fazil & Ipek, 2013;Karki & Aryal, 2019). The study highlighted idiosyncratic risk as a significant component of total volatility.…”
Section: Idiosyncratic Riskmentioning
confidence: 99%
“…Traditionally, the Capital Asset Pricing Model (CAPM) has focused on systematic risk, overlooking firm-specific (idiosyncratic) risk, which can't be diversified away. However, in practical scenarios where portfolio diversification isn't feasible, investors must account for idiosyncratic risk alongside systematic risk in predicting expected returns (Fazil & Ipek, 2013;Karki & Aryal, 2019). The study highlighted idiosyncratic risk as a significant component of total volatility.…”
Section: Idiosyncratic Riskmentioning
confidence: 99%
“…As also shown in previous studies, due to the recession in the crisis period, high volatility was found in the markets, which is directly associated with strong correlations between markets. Idiosyncratic risk was the biggest component of overall risk during the period of GFC (Fazil and ˙Ipek 2013).…”
Section: Impact Of Crises On Risk Diversificationmentioning
confidence: 99%
“…In reality however, this is not always the case. Studies has also found that, for some reasons, investors always do not hold diversified portfolio which usually eliminate significantly idiosyncratic volatility as supported by CAPM (Fazil, 2013), and idiosyncratic risk is priced to compensate investors for their inability to hold the market portfolio (Fu, 2009;Eiling, 2008;Fazil, 2013;Boloorforoosh, 2014). With increasing number of empirical studies indicating that financial accounting information affect stock prices volatility (Yu and Huang, 2005;Sharma, 2011;Glezakos, 2012;Sibel, 2013), and with the growth of NSE over the decade, more specificly the growth of active investors, equity turnover and market capitalization; which has led to increased stock price movement and market volatility (Kihara, 2011), there is need to investigate the effect of published financial statement information on idiosyncratic volatility equities price listed at the NSE.…”
Section: Problem Statementmentioning
confidence: 99%
“…Studies has also found that, for some reasons, investors always do not hold diversified portfolio which usually eliminate significantly idiosyncratic volatility as supported by CAPM (Fazil, 2013). Goetzman and Kumar (2008) found that 25% of investors hold only one stock, and 50% of investor portfolios contained less than 3 stocks while less that 10% of their portfolios contain less than 10 stocks.…”
Section: Introductionmentioning
confidence: 98%